Conditioning swimmers: aerobic and anaerobic responses to controlled frequency breathing under watchful eye - Town, G. P.; Vanness, M. J. (Swimming Technique, 1990)
Fourteen Wheaton College swimmers in peak condition performed tethered swimming under increasing resistance loads. Different rates of controlled frequency breathing (CFB) were used. CFB is a form of hypoxic training (breathing occurs less often than normal). Coaches maintain that this form of training improves both aerobic and anaerobic adaptation as well as developing a tolerance for higher levels of blood lactate. This study failed to show a relationship between CFB and elevated blood lactate levels. Under the condition of breathing once every eight strokes VO2 was not maintained. There was a proportional decrease in ventilation associated with increased breathing restriction, but tidal volume increased as a compensatory response. As CFB increased, stroke mechanics worsened (the rate increased as CFB increased). Implication: There appears to be no positive training effect or value to using CFB as a training activity. It may be counter-productive. Since the swimmer needs to compensate for the loss of breath by increasing the amount of strokes used, concentration on technique deteriorates. Worsening a technique has no value.